Fruit and Vegetable Storage Hypobaric, Hyperbaric and Controlled Atmosphere - Thompson, Anthony Keith; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This Brief reviews the effects of increasing and reducing atmospheric pressure on the postharvest life of fruit and vegetables. The text covers the common methods and technologies used and evaluates the history and benefits of hypobaric and hyperbaric storage. Both of these techniques have the potential to address quantitative and qualitative challenges in the postharvest sector of the fresh fruit and vegetables industry. Hypobaric and Hyperbaric Storage of Fruit and Vegetables reports on the effects of storage on over 45 types of fruit and vegetables, as well as on whole plants and cut flowers. As consumer demand for high quality product increases, proper postharvest storage will continue to gain in importance. The environmental conditions used in storage have a vital influence on the quality, safety and health benefits of fruit and vegetables.
Storage -- Controlled Atmosphere Storage -- Hypobaric Storage -- Hyperbaric Storage -- Conclusions.
Keywords: Food science; Agriculture; Food Science; Agriculture